FIRST REPORT OF THE PRESENCE OF THE GENUS DIGITONTHOPHAGUS (COLEOPTERA: SCARABAEIDAE) IN COLOMBIA - NORIEGA-A. JORGE ARI (Caldasia)
The presence, migration, and distribution of the Dung Beetle Digitonthophagus gazella (Fabricius 1787) (originally the species was named Onthophagus gazella Fabricius, and later placed on the Digitonthophagus genus by the Zunino (1981) review)